2020
DOI: 10.1038/s41419-020-2384-5
|View full text |Cite
|
Sign up to set email alerts
|

“Iron free” zinc oxide nanoparticles with ion-leaking properties disrupt intracellular ROS and iron homeostasis to induce ferroptosis

Abstract: Exposure to nanomaterials (NMs) is an emerging threat to human health, and the understanding of their intracellular behavior and related toxic effects is urgently needed. Ferroptosis is a newly discovered, iron-mediated cell death that is distinctive from apoptosis or other cell-death pathways. No evidence currently exists for the effect of "iron free" engineered NMs on ferroptosis. We showed by several approaches that (1) zinc oxide nanoparticles (ZnO NPs)-induced cell death involves ferroptosis; (2) ZnO NPs-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 57 publications
5
55
0
2
Order By: Relevance
“…For example, zinc can enhance mitochondrial ROS generation [ 7 ], induce lipid peroxidation and trigger ferroptosis via the phosphorylation of xCT [ 8 ]. Consistent with our results, “iron-free” zinc oxide nanoparticles also trigger ferroptosis via increasing ROS, lipid oxidation, and depleting glutathione [ 9 ]. While it is still possible that zinc affect ferroptosis through regulating iron levels, multiple independent studies on the essential role of zinc in ferroptosis may prompt re-examinations of the central role of iron in ferroptosis as implied in the name of this form of regulated cell death.…”
Section: Unexpected Role Of Zinc and Zip7 In Ferroptosissupporting
confidence: 90%
“…For example, zinc can enhance mitochondrial ROS generation [ 7 ], induce lipid peroxidation and trigger ferroptosis via the phosphorylation of xCT [ 8 ]. Consistent with our results, “iron-free” zinc oxide nanoparticles also trigger ferroptosis via increasing ROS, lipid oxidation, and depleting glutathione [ 9 ]. While it is still possible that zinc affect ferroptosis through regulating iron levels, multiple independent studies on the essential role of zinc in ferroptosis may prompt re-examinations of the central role of iron in ferroptosis as implied in the name of this form of regulated cell death.…”
Section: Unexpected Role Of Zinc and Zip7 In Ferroptosissupporting
confidence: 90%
“…One of critical ferroptosis hallmarks is lipid peroxidation ( 20 , 21 , 45 ). The interplay between lipids and intracellular ROS represents a fundamental process in ferroptosis ( 20 , 46 , 47 ). Evidence from our recently published study has revealed that intracellular ROS production is substantially elevated in 661W photoreceptor cells at 6 h after exposure to 5-μM atRAL ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of biotoxicity of nanomaterials is multifaceted and unclear. Among them, the oxidative stress caused by the production of a large amount of ROS is considered to be one of the possible mechanisms of its toxic effects 47 . In the physiological state, the expression level of ROS keeps dynamic balance.…”
Section: Discussionmentioning
confidence: 99%